Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1038/hdy.1988.40
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and the outcrossing rate in natural populations of Allium schoenoprasum L. (wild chives)

Abstract: The level of inbreeding depression has been measured at four independent stages of the life cycle (parental seed fecundity, seed viability, seedling survival and seedling growth. rate) using wild-collected parental plants from seven natural populations of Allium schoenoprasum. At each stage, progenies produced by self-fertilisation were significantly less fit than progenies produced by cross-fertilisation, and the overall inbreeding depression was severe (0.718). This suggests that a high level of cross-fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…Complete or selective abortion of ovules was observed in S. sesban, S. kinensis and S. geotzei (Heering, 1994). This phenomenon was also reported by Stevens and Bougourd (1988), when they estimated as 0.91 for Allim schoenoprasum L. that is, a clonal, selfcompatible hermaphrodite plant with apparently ample opportunities for geitonogamous selfing. Barnes et al (1972) reported that the frequency of ovule abortion is greater in zygotes and embryos resulting from selfpollination than from cross-pollination.…”
Section: Discussionsupporting
confidence: 52%
“…Complete or selective abortion of ovules was observed in S. sesban, S. kinensis and S. geotzei (Heering, 1994). This phenomenon was also reported by Stevens and Bougourd (1988), when they estimated as 0.91 for Allim schoenoprasum L. that is, a clonal, selfcompatible hermaphrodite plant with apparently ample opportunities for geitonogamous selfing. Barnes et al (1972) reported that the frequency of ovule abortion is greater in zygotes and embryos resulting from selfpollination than from cross-pollination.…”
Section: Discussionsupporting
confidence: 52%
“…In some plant species, seed weight is a good indicator of seed viability and seedling growth rate (Stanton, 1984), although Stevens and Bougourd (1988) did not find such a relation in Allium schoenoprasum. We compared cross-fertilization and self-fertilization to find out whether there was a different weight investment in capsules in L.…”
Section: Discussionmentioning
confidence: 99%
“…Self-fertilization and inbreeding depression have been widely studied, from both a theoretical and an empirical point of view (Lloyd, 1979;Lande and Schemske, 1985;Charlesworth and Charlesworth, 1987;Holsinger, 1988;Schemske and Lande, 1985;Stevens and Bougourd, 1988). Most studies are limited to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Fecundity estimates of plants which survived to reproduce, and fitness estimates for all plants, as in Table 6. 1979; Price and Waser, 1979;Gouyon and Vemet, 1980;Schemske, 1983;Jolls, 1984;Kesseli and Jain, 1984;Levin, 1984;Schemske and Pautler, 1984;Harder et al, 1985;Stevens and Bougourd, 1988), but some exceptions are known where seed set following self-pollinations was not less than seed set ofoutcrossed flowers (Schoen, 1983;Karron, 1989).…”
Section: Discussionmentioning
confidence: 99%